Images of eternal beauty in funerary verse inscriptions of the Hellenistic and Greco-Roman periods - Wypustek, Andrzej. (Mnemosyne, Supplements, 2013)
In 'Images of Eternal Beauty in Funerary Verse Inscriptions of the Hellenistic and Greco-Roman Periods Andrzej Wypustek provides a study of various forms of poetic heroization that became increasingly widespread in Greek funerary epigram. The deceased were presented as eternally young heroes, oblivious of old age and death, as stars shining with an eternal brightness in heavens or in Ether, or as the ones chosen by the gods, abducted by them to their home in the heavens or married to them in the other world (following the examples of Ganymede, Adonis, Hylas and Persephone). The author demonstrates that, for all their diversity, the common feature of these verse inscriptions was the praise of beauty of the dead.